Некоторые морфологические закономерности роста шаровковых - Стадниченко, А.П. (Вестник зоологии, 1979)
The paper deals with some size characteristics of orb shells (Sphaeriidae Bourg, 1883) which are of a definite taxonomic value and with peculiarities of their shells growth. It is determined that orb shells of the Crimea are characterized by both positive and negative allometry. Ratios between the height and length as well as between the shell convexity and length may be expressed by the formulas H=ₐLᒃ and S=ₐ₁Lᒃ¹. Indices of a relative growth in height and convexity of the orb shells with an increase in their length by a unit are determined.